IMPLEMENTATION AND IMPLICATIONS OF WORSHIP HABITATION IN BASIC EDUCATIONAL SETTING (a Case Study of Worship Habituation Effort at SDN 2 Yogyakarta Gading Rejo Pringsewu) - Budianti, Era; Farhan, Muhammad; Sahroni, Mahmud (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2021)
Habituation in education is very important especially in personal and moral formation as it instill positive elements in students' growth. The more religious experience a student gets through habituation, the more religious values are in his personality and the easier it is for him to understand religious teachings. This study focuses on the Implementation and Implications of Worship Habituation in the Educational Context, which is at SD Negeri 2 Yogyakarta, Gading Rejo Pringsewu. This research used descriptive qualitative method. The primary data sources are the principal, Islamic studies teachers , and fifth grade students. Data analysis for this research uses three steps, namely data reduction, data display and conclusion drawing/verification. The result shows that the effort in increasing the intensity and quality of worship activities through habituation at SD Negeri 2 Yogyakarta is quite effective, especially in increasing awareness in carrying out worship. The majority of students have shown an increase in their self - awareness on worship practices that are consistently being implemented not only at school, but also outside of school. The habituation program implemented in schools will become a consistent habit and an inseparable part in the activities and the learning system and  also become the identity of this institution.